STRATEGI PEMASARAN PT. PEGADAIAN (PERSERO) UPC LAPE DALAM MEMPERTAHANKAN MARKET SHARE - K Kamaruddin; I Ismawati; Fitri Anggraini (Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine the marketing strategy of PT. Pegadaian (Persero) UPC Lape in maintaining market share. The type of this study was descriptive study. The data used were qualitative and quantitative data. The sources of data in this study were primary and secondary data. The tools used to collect data were interviews, documentation, and questionnaires. The population and sampel are divided into three parts, namely: employees, customers, and lecturers. The numbers of samples in this study were 30. The technique of data analysis was process Hierarchy Analysis Technique (AHP). The results of the study showed that Marketing Strategy of arketing strategy of PT. Pegadaian (Persero) UPC Lape in maintaining market share used all elemnts of marketing srategies such as STP (Segmenting, Targeting, and Positioning), Marketing Mix 7P (Product, Price, Place, Promotion, People, Process, and Physical Evidence). The priority marketing strategies that can be implemented using the Marketing Mix strategy include product, price, place, promotion, people, process, and physical evidence. The price strategy received the highest score in this study, making it a priority marketing strategy in PT. Pegadaian (Persero) UPC Lape to maintain market share. Through the implementation of the right price strategy, it will be able to attract customer interest to make transactions, thereby increasing market share and providing optimal profits for PT. Pegadaian (Persero) UPC Lape.